Perceived Employability and Entrepreneurial Self-Efficacy As Predictors Of Entrepreneurial Intention Among University Graduates in Anambra State - Okafor, Rachael Amaka; Chine, Bernard Chukwukelue; Oguegbe, Tochukwu Matthew (Practicum Psychologia, 2024)
This study investigated perceived employability and entrepreneurial self-efficacy as predictors of entrepreneurial intention among university graduates and job seekers in Anambra state, Nigeria. Recently, the increasing rate of unemployment plaguing most nation of the world is alarming, being an entrepreneur is challenging, half of all startups fail within the first four years and only about 25 per cent survive the first ten. Therefore, the need to consider entrepreneurial intentions is significant for nation building. The analysis found out that there are many factors such as poor enabling business environment, lack of capital, poor business facilities, stringent process in accessing grants and loans etc. These factors have dampened the morale of some business-oriented graduates, which have made many of them to be skeptic about their skills and abilities in entrepreneurship. Based on the aforementioned, four hundred and fifty-seven (457) beneficiaries were conveniently drawn from N-Power youth empowerment scheme in Awka, Anambra State. The participants comprise 265(57.99%) males and 192(42.01%) females, with ages ranging from 22-35 years, and with a mean age of 30.5 years and standard deviation of 4.42. The result of the study showed that perceived employability (β = .37, ΔR2 = .13, p < .041) significantly predicted entrepreneurial intention, and entrepreneurial self-efficacy significantly predicted entrepreneurial intention (β = .17, ΔR2 = .02, p < .038). In conclusion, it could be inferred that having possessed the required job skills and experience can help one discover his or her entrepreneurial potentials and even think towards that direction. Also, being confident in one’s ability can help him or her carry out business ideas and possibly achieve his or her entrepreneurial intention. It is recommended that trainings and workshops related to the acquisition of entrepreneurial skills should be encouraged.